REFLEKSI LAPORAN ZIS BERDASARKAN PSAK 109 DAN PENGARUHNYA TERHADAP KEPERCAYAAN MUZAKKI AL-JIHAD - Lazia, Hanefi Mami; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the form of management and reporting of ZIS funding and to analyze how the presentation of the fund statement in an institution aof amil zakat with the level of trust of the donors (muzakki). Meanwhile on the other side, the researcher is also observed in depth of the level trust of the donorsin selecting an institution of amil zakat if the fund statement is not a priority reason for a donor in selecting his decision. The method has been done by using qualitative method (descriptive explorative) in which the paradigm has been carried out by using interpretative paradigm and an open-ended interview. The result of the research shows that the form of management of zakat fund, infaq and shadaqah in Al-Jihad Social Funds Foundation is not in accordance with the regulation of PSAK No. 109. It gives significant influence to the level of trust of the donors (muzakki). The middle low level group, these people tend to be ignorant. But the middle up and high class they tend to be critical. The findings in the field show that the differences in point of views are influenced by educational and work background. Moreover, the donors (muzakki) who come from various groups have their similarity i.e the level of trust which has been influenced by the level of their religiosity, and not from the level of income or even from the current system of fund statement.Keywords: zakat, infaq, shadaqah, donors, institution of amil zakat.